2021
DOI: 10.4013/base.2021.181.03
|View full text |Cite
|
Sign up to set email alerts
|

Economic Value Drivers for Brazilian Agricultural Cooperatives

Abstract: This article aims to identify the economic value drivers for Brazilian agricultural cooperatives. To this end, we analyzed the potential value drivers for agricultural cooperatives in Paraná and Rio Grande do Sul using panel data regression, considering data from 2008 to 2016. The results showed that net margin, basic purchasing power, investment in fixed assets, circulating assets X sales margin, fixed asset turnover, net revenue, and number of members are the economic value drivers for Brazilian agricultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several value drivers' classifications can be found in academic literature: macro drivers versus micro value drivers (Rappaport, 2001), financial drivers versus non-financial drivers (Young & O'Byrne, 2003), differentiating capabilities drivers versus financial strategy drivers (Assaf, 2014). By analyzing the academic literature, Figari et al (2021) identified qualitative and quantitative empirical research on value drivers, mostly quantitative research applied to public non-financial companies that aim at identifying value drivers and analyzing their relationship with business value.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Several value drivers' classifications can be found in academic literature: macro drivers versus micro value drivers (Rappaport, 2001), financial drivers versus non-financial drivers (Young & O'Byrne, 2003), differentiating capabilities drivers versus financial strategy drivers (Assaf, 2014). By analyzing the academic literature, Figari et al (2021) identified qualitative and quantitative empirical research on value drivers, mostly quantitative research applied to public non-financial companies that aim at identifying value drivers and analyzing their relationship with business value.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Changes in the institutional environment, such as globalization, technological development (Young & O'Byrne, 2003), high competitiveness, and economic crises (Russo & Parisi, 2017), cause a culture of wealth creation for investors, which has contributed to organizational continuity (Assaf Neto, 2014;Russo & Parisi, 2017). Value-based management (VBM) has been a prominent model in the academic literature on shareholder wealth creation (Figari et al, 2021) that maximizes company value to shareholders, increasing the economic value to the investor (Kumar, 2015;Russo & Parisi, 2017). MacDiarmid et al (2017) emphasize the importance of identifying value drivers, as they contribute to financial strategies definition for shareholder value creation.…”
Section: Introductionmentioning
confidence: 99%